Causality Evidence of Exchange Rate - Stock Price Relation in Nigeria: Symmetric and Asymmetric Approach - Gbadebo, Adedeji (Acta Universitatis Danubius. Œconomica, 2023)
Foreign exchange and stocks are the two most traded financial assets in the world. The causality between their prices has been subject of research, particularly, on whether it is exchange rates that drive stock prices, as suggested by flow-oriented models from Dornbusch and Fisher (1980) or it is stock prices that drive the exchange rates, as suggested by the flow-oriented models from that Frankel (1983). I use data, from Nigeria, to explore Granger causality between them based on the symmetric approach, from Toda-Yamamoto (1995) and the asymmetric approach, from Hatemi-J (2012), for handling connectedness for ergodic variables with deterministic trends. The empirical test completed, as reveal by the unit root confirmation, identifies that the two considered series are trended and integrated. The results from the symmetric method recognise causality from exchange rate to the stock price, with no potential Granger-causal feedback. I transform the integrated series into negative and positive cumulative fragments, and complete the asymmetric test using the Wald statistic to verify the likelihood of lopsided causality. The results identify that allowing for asymmetry, and in particular, positive shocks in the naira exchange rate can cause a positive shock in share price, and not vice versa. Also, negative shocks in the exchange rate would not cause a negative shock in share price. This implies that any depreciation or devaluation of the naira would motivate investors to increase their participations in the stock exchange market. These finding has vital policy implications to different stakeholders, including government, regulators, currency- and stock markets traders and others in the Nigerian context.